Redescription of Oedichirus flammeus Koch, and description of two new Oedichirus species from China (Coleoptera, Staphylinidae, Paederinae, Pinophilini) - Li, Wen-Rong; Xie, Nan-Nan; Li, Li-Zhen (Zootaxa, 2015)
Oedichirus flammeus Koch, 1939 (Zhejiang, East China), O. damingensis sp. n. (Guangxi, South China), and O. pengzhongi sp. n. (Hainan, South China) are (re-)described and illustrated. The genus is now represented in China by eight described species, six of them are micropterous. The latest key to the Oedichirus species of China is modified to include the new species.